Step-by-step explanation:
Step-by-step explanation:
\begin{gathered} \frac{8x - 3}{3x} = 2 \\ 8x - 3 = 6x \\ 8x - 6x = 3 \\ 2x = 3 \\ x = \frac{3}{2} \end{gathered}
3x
8x−3
=2
8x−3=6x
8x−6x=3
2x=3
x=
2
3
Answer:
x = -11
Step-by-step explanation:
First, add three to both sides on the equation. Then, your equation becomes 55= -5x. Finally, divide both sides by -5 to get -11 = x. So, x equals -11. Hope this helps!
Answer:
uhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhhh
Step-by-step explanation: